IDENTITAS VISUAL BUDAYA JEPANG DALAM MANGA DEMON SLAYER: KIMETSU NO YAIBA - Ramdhan, Asep; Prayoga, Candra (Department of Interior Design, Faculty of Engineering, Lancang Kuning University, Indonesia, 2025)
The manga